Relationship between Leadership Style and Characteristics of Room Head and Nurses' Performance - Aris Teguh Hidayat; Masniati Arafah; Lindesi Yanti; Fermata Sari (Indonesian Journal of Global Health Research, 2025)
Nursing services have a close relationship with nurse performance, which is influenced by various factors, including leadership style and characteristics of the head of the room. A good leadership style can create positive work effectiveness, while ineffective leadership often triggers complaints about health services. This study aims to determine the relationship between leadership style and characteristics of the head of the room with nurse performance at the dr. AK Gani Military Hospital, Palembang. This study used a correlational design with the Cross-Sectional method. The study sample consisted of 131 nurses taken using a purposive sampling technique. Data were collected using a questionnaire and analyzed using the Chi-Square test. The results showed a significant relationship between leadership style and nurse performance (p = 0.003) and between the characteristics of the head of the room and nurse performance (p = 0.004). In conclusion, leadership style and characteristics of the head of the room have an important role in influencing nurse performance. This study is expected to provide benefits for the development of nursing management, especially in improving the quality of leadership of the head of the room to support optimal nurse performance.